Stork’s bill (Erodium cicutarium (L.) L’Her. ex Ait) and hemp-nettle (Galeopsis tetrahit L.): a cautionary note for eastern Canada field crops - Légère, Anne; Stevenson, Craig; Lalonde, Olivier; Vanasse, Anne; Benoit, Diane (Phytoprotection, 2010)
Stork’s bill was observed for the first time in 2009, and again in 2010, in a 22-yr-old conservation tillage study at La Pocatière, Québec. Within a year, the species had spread from two to ten plots, with densities ranging between 100 and 232 plants m-2 in 2010 compared with ≤ 12 plants m-2 in 2009. Currently, stork’s bill is not a major agricultural weed in eastern Canada; it should therefore be monitored closely and acted upon rapidly to prevent its establishment and spread. The relatively high hemp-nettle density in no-till compared with tilled treatments in 2009 was attributed to a cultivation operation conducted exceptionally in no-till treatments, confirming the responsiveness of the species to tillage.